A Multi‐Bioactive Nanomicelle‐Based "One Stone for Multiple Birds" Strategy for Precision Therapy of Abdominal Aortic Aneurysms. Issue 44 (3rd October 2022) - Lin, Wenjie; Hu, Kaiyao; Li, Chenwen; Pu, Wendan; Yan, Xinhao; Chen, Haiyan; Hu, Houyuan; Deng, Hongping; Zhang, Jianxiang
Abstract: Abdominal aortic aneurysm (AAA) remains a lethal aortic disease in the elderly. Currently, no effective drugs can be clinically applied to prevent the development of AAA. Herein, a "one stone for multiple birds" strategy for AAA therapy is reported. As a proof of concept, three bioactive conjugates are designed and synthesized, which can assemble into nanomicelles. Cellularly, these nanomicelles significantly inhibit migration and activation of inflammatory cells as well as protect vascular smooth muscle cells (VSMCs) from induced oxidative stress, calcification and apoptosis, with the best effect for nanomicelles (TPTN) derived from a conjugate defined as TPT. After intravenous delivery, TPTN efficiently accumulates in the aneurysmal tissue of AAA rats, showing notable distribution in neutrophils, macrophages and VSMCs, all relevant to AAA pathogenesis. Whereas three examined nanomicelles effectively delay expansion of AAA in rats, TPTN most potently prevents AAA growth by simultaneously normalizing the pro‐inflammatory microenvironment and regulating multiple pathological cells. TPTN is effective even at 0.2 mg kg −1 . Besides, TPTN can function as a bioactive nanoplatform for site‐specifically delivering and triggerably releasing anti‐aneurysmal drugs, affording synergistic therapeutic effects. Consequently, TPTN is a promising multi‐bioactive nanotherapy and bioresponsive targeting delivery nanocarrier for effective therapy of AAA and other inflammatory vascular diseases. Abstract : A "one stone for multiple birds" strategy is proposed for therapy of abdominal aortic aneurysm (AAA). Three engineered conjugates can assemble into nanomicelles capable of inhibiting migration/activation of inflammatory cells and protecting smooth muscle cells from oxidative stress, calcification, and apoptosis. Intravenously delivered nanomicelles efficiently accumulate in aneurysms of rats and distribute in multiple pathological cells, thereby alleviating AAA progression.